Organizational Capital - Thijanul Aroby; M. Isa Anshori (Universitas 45 Surabaya, 2024)
Forming a good organization certainly requires a strong foundation, one of which is organizational capital. Organizational capital is a collection of internal resources and capabilities of an organization that are characteristic and able to improve the organization's ability to achieve its goals, in other words, organizational capital is a facility and infrastructure that supports workers so that they can carry out their duties with dedication. So this is very important to study together considering its very crucial impact on human resources in an organization. So the purpose of this study is to understand the various criteria related to organizational capital and why it is important to apply it in an organization. This research is a type of literature research where this research is a process consisting of a series of activities to obtain and process information obtained from various literary sources such as books, magazines, scientific journals, newspapers, and others. The results of this study show that if organizational capital does not exist, the company cannot grow or even operate. The true strength of a company lies in its human resources. Therefore, companies must optimize the use of human resources to become a crucial and reliable asset..